2006
DOI: 10.1536/ihj.47.727
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacity, Skeletal Muscle Strength, and Skeletal Muscle Volume in Patients With Myocardial Infarction

Abstract: SUMMARYPrevious studies have reported that skeletal muscle strength is closely related to exercise capacity in patients with myocardial infarction (MI). However, none of the previous studies have fully investigated the correlation between exercise capacity and the skeletal muscle volume (MV). Seventy patients with MI underwent symptom-limited cardiopulmonary exercise testing using a treadmill. The MV was evaluated by electrical impedance analysis and the maximal knee extension strength (Peak torque: PT) was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…8,10,11,21 However, the relationship between muscle strength and exercise capacity in CAD patients has been evaluated only in small patient groups, with contradictory results. 9,[13][14][15]22 The present study is the first o systematically examine the association between maximal QIS and exercise capacity in a large cohort of CAD patients. Our results show that maximal QIS was among the strongest independent predictors of each exercise capacity category after adjusting for several confounding factors.…”
Section: Maximal Qis and Exercise Capacity In Cad Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…8,10,11,21 However, the relationship between muscle strength and exercise capacity in CAD patients has been evaluated only in small patient groups, with contradictory results. 9,[13][14][15]22 The present study is the first o systematically examine the association between maximal QIS and exercise capacity in a large cohort of CAD patients. Our results show that maximal QIS was among the strongest independent predictors of each exercise capacity category after adjusting for several confounding factors.…”
Section: Maximal Qis and Exercise Capacity In Cad Patientsmentioning
confidence: 98%
“…6,20 Several papers have assessed the relationship between quadriceps strength and exercise capacity in normal subjects and chronic heart failure patients, 11,12,21 but such relationship has been addressed to date only in small groups of patients with coronary artery disease (CAD) with contradictory results. 9,[13][14][15]22 Our working hypothesis was that a positive correlation would exist between maximal quadriceps isometric strength (QIS) and exercise capacity in CAD patients and that, if this were true, such a relationship would provide useful information in the clinical setting for a strength training prescription tailored on daily habitual activities in this population. The purpose of the present study was thus to investigate the relationship between maximal QIS and exercise capacity and to identify the levels of maximal QIS corresponding to those of given habitual activities in a large cohort of patients with CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the lower limb muscle function is an important peripheral factor in cardiac function [3][4][5][6][7][8]. Our previous study has concluded that exercise capacity in patients with myocardial infarction (MI) was determined by the strength and volume of the skeletal muscle [3].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the relationship between the skeletal muscle volume, strength and exercise capacity was investigated in patients with MI who performed CR program in the acute phase [3]. Unfortunately, our previous study result was insufficient to evaluate the change of skeletal muscle volume and strength by exercise training and the influence of CR program.…”
Section: Introductionmentioning
confidence: 99%